Johnny Boo finds a clue? - Kochalka, James (Kochalka, James. Johnny Boo, 2020)
"The Eisner-Award-winning Johnny Boo series just keeps getting wilder and funnier! This time, a secret thief has stolen Johnny Boo's ice cream. Armed with his mighty magnifying glass, Johnny Boo will find all the clues and capture the vicious villain. The main suspect is a purple mountain whose peak looks suspiciously like it might be covered in vanilla ice cream. To battle this giant foe, Johnny Boo and his friends must team up and transform into their ultimate form: the MEGA JOHNNY ULTRA-BOO! ...But what if the mountain is innocent?"--Provided by publisher.